Evaluation of fucoidan from Sargassum duplicatum on performance immune responses, serum biochemical, and hematological testing in rats - Ellya Sinurat, Endar Marraskuranto, Subaryono Subaryono (Journal of Applied Pharmaceutical Science, 2021)
This study investigates the hematological and serum biochemical effects of the fucoidan to ascertain the safety of fucoidan from Sargassum duplicatum. Fucoidan from S. duplicatum was extracted using water as a solvent and precipitated with calcium chloride. The parameters of the fucoidan quality test included water content, total carbohydrate, total sulfate, moisture content, and uronic acid. The extract was used for in vivo immunostimulant test using Sprague Dawley rats for 14 days with four treatments. The experimental rats were fed with fucoidan solvent as a control (P0) and fucoidan for the treatment at a dose of 1 (P1), 2 (P2), and 4 g/kg body weight (BW) (P3). Serum biochemical and hematological test parameters included liver function [(serum glutamic-pyruvic transaminase () and glutamic-oxoloacetic transaminase ()]), kidney function, red blood counts, and white blood differentials. The results of the chemical composition of fucoidan show that it contains uronic acid of 0.28%, sulfate of 11.2%, moisture content of 8.25%, and total polysaccharide of 60.5% ± 4.5%. Immunostimulant activity results showed an increase in macrophage activity in the fucoidan-treated rats but did not affect kidney function. In vivo immunostimulant test results in white rats show that giving fucoidan 1 g/kg BW can increase the immune system two times higher.
Keywords: Fucoidan, Sargassum duplicatum, immunomodulatory, macrophages, Toxicity